Effects of Supplemental Dietary Phytase and 25-Hydroxycholecalciferol on Excreta Characteristics and Nutrient Content from Commercial Layers Inoculated Before or at the Onset of Lay with the F-Strain of Mycoplasma gallisepticum - Miles , D.M.; Branton, S.L.; Peebles, E.D.; Burnham, M.R.; Brooks, J.P.; Moore, Jr., P.A. (International Journal of Poultry Science, 2021)
Background and Objective: To sustain commercial egg production, innovative dietary inputs, their interaction with disease control agents and effects on all aspects of the production system and bird health must be investigated. The objective of the current study was to ascertain the effects of F-strain Mycoplasma gallisepticum (FMG) inoculation in conjunction with supplemented diets on excreta characteristics and nutrient content as hens age. Materials and Methods: Commercial layer diets were supplemented with phytase and 25-hydroxycholecalciferol to determine the effects on excreta from 39-55 week of age for hens that were inoculated (or sham inoculated) with FMG at 12 week (prelay) or at 22 week (onset of laying cycle). Basal vs. supplemented diets, type of inoculation (FMG vs. sham) and age of inoculation were compared. In two trials, layer excreta were collected at 39, 43, 47, 51 and 55 week of age where moisture content, pH, N, C, Ca, K, Mg, Na, P, Cu, Fe, Mn and Zn concentrations were determined. Statistical assessments were performed using a mixed linear model to accommodate both the fixed- and random-effects parameters. Results: Fecal moisture, pH, total N, or total C were not affected by diet, inoculation age, or inoculation type. The results showed that fecal moisture content decreased (83-79%) while total N (35.8 to 54.6 g kg–1), total C (317-339 g kg–1), K (22.8-27.1 mg kg–1) and Zn (552-794 mg kg–1) generally increased with hen age. Conclusion: Of the studied parameters, only hen age affected these excreta characteristics. Integrators need not be concerned that phytase/25-hydroxycholecalciferol supplemented diets or FMG inoculation will incur manure handling changes relative to nutrient or mineral content.